ORGANOLEPTICS TEST FOR MELON CULTIVATION WITH CHLORELLA PYRENOIDOSA MICROAGAE BASED FERTILIZER - MARGARETHA PRABA AULIA; RANGGA WARSITA AJI; JUJUK JUHARIAH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Melon cultivation is not easy and requires intensive handling because melon plants are sensitive to environmental changes and are susceptible to disease. The use of Chlorella pyrenoidosa microalgae-based fertilizer is one of the breakthroughs that have been made by researchers in helping melon cultivation. This microalgae fertilizer is intended for nutrient fulfillment as well as controlling soil pH. People are still very unfamiliar with the use of this Chlorella Pyrenoidosa microalgae-based fertilizer. It is necessary to carry out further analysis of the use of microalgae Chlorella Pyrenoidosa as fertilizer, especially for use in melon cultivation. The analysis carried out was to see the results of the preference test based on the organoleptic test of the melon itself with the use of Chlorella Pyrenoidosa fertilizer. It is intended that the community, especially melon farmers, can have more knowledge about this microalgae-based organic fertilizer. The feasibility test of the results was carried out by the organoleptic test method on 30 respondents with different age variations on the preferences for melons produced by each treatment. Organoleptic test includes testing of the color, smell, taste, and texture of each melon produced by each treatment. Organoleptic data were analyzed using SPSS using the One Way Anova method and followed by Duncan's analysis. The use of Chlorella Pyrenoidosa microalgae fertilizer did not have a significant difference to the organoleptic test on its use in melon cultivation. This can be used as an option for farmers to use Chlorella Pyrenoidosa microalgae fertilizer as a substitute fertilizer for melon cultivation.